Democratic Schools and Institutional Coherence - Amador Guarro (Universidad Autónoma de Madrid, 2016)
The thesis we defend in this article is: a democratic school has to be essentially fair. School justice involves, among others, an ethics of criticism, which includes the removal of barriers to learning for all students, and especially for most disadvantaged students. To remove these barriers, the school has to constantly advance the democratic construction of its own institutional coherence. And, in the context of institutional coherence, school should pay special attention to the curriculum coherence.